Diabetic complications and oxidative stress: The role of phenolic‐rich extracts of saw palmetto and date palm seeds. Issue 11 (4th September 2020) - Barakat, Amal Z.; Bassuiny, Roqaya I.; Abdel‐Aty, Azza M.; Mohamed, Saleh A.
Abstract: Recently, we reported that the date palm seed (DP) and saw palmetto seed (SP) extracts possessed a great amount of phenolic contents with potent antioxidant, antimicrobial, and anti‐inflammatory activities. Therefore, this study aimed to assess the role of DP and SP phenolic‐rich extracts in modulating diabetic complications and oxidative stress in the STZ‐ diabetic rat. DP and SP extracts significantly inhibited both microbial and pancreatic α‐amylases. The STZ‐induced diabetic rat groups treated with DP and SP extracts exhibited reversed hyperglycemia (40% and 54%, p < .001–.01) and body weight (70%, p < .001) alteration close to normal. Moreover, DP and SP extracts modulated serious damages in the structures of the pancreas, kidney, and liver of diabetic rats. DP and SP extracts improved the decline of the activities of antioxidant enzymes: Catalase, glutathione‐S‐transferase, glutathione reductase, and glutathione peroxidase in liver, kidney, and pancreas of the diabetic rats. Practical applications: Generally, date seed is a rich source of dietary fibers, polyphenols, and antioxidants and used in foods and pharmaceuticals. Our study reported that date palm seed (DP) and saw palmetto seed (SP) phenolic‐rich extracts attenuated diabetes and its complications, probably tissue regeneration and normalizing the oxidative stress in the STZ‐induced diabetic rat. Abstract : The STZ‐induced diabetic rat groups treated with DP and SP phenolic‐rich extracts exhibited reversed hyperglycemia and body weight alteration close to normal. DP and SP extracts modulated the serious damages in the structures of the pancreas, kidney, and liver of diabetic rats. DP and SP extracts improved the decline of the activities of antioxidant enzymes.